The Veil, Purdah, and Their Relevance to The Role of Muslim Women in The Archipelago: A Historical Study - Elfando, Mario Excel; Hannase, Mulawarman (JURNAL ISLAM NUSANTARA, 2023)
Face veil has become an issue often discussed nowadays, including in Nusantara. The face veil is often rejected or discriminated against because it is considered part of the seclusion system (purdah) that limits the role of women and is not by the culture of Nusantara. This study aims to describe the face veil and purdah traditions in the history of Nusantara and analyze whether the face veil in Nusantara is part of purdah (seclusion). This research uses a descriptive-analytical method and a qualitative approach. Data are collected by literature review and online interviews. The results indicate that the veil and purdah were once part of the history of Nusantara. The face veil is known in Malay culture as tudung lingkup, in the Ocu tradition as maroguok, and the Mbojo tradition as rimpu colo. It is concluded that wearing the veil is only sometimes identic with the domestication of women's roles. It depends on the cultural conditions adopted by each community. In addition to the domestic role, the role that is also dominant for veiled women is the productive role.